Modulation of inflammatory processes by thermal stimulating and RPE regenerative laser therapies in age related macular degeneration mouse models. Issue 3 (September 2020) - Richert, Elisabeth; von der Burchard, Claus; Klettner, Alexa; Arnold, Philipp; Lucius, Ralph; Brinkmann, Ralf; Roider, Johann; Tode, Jan
Abstract: Purpose: Inflammatory processes play a major role within the multifactorial pathogenesis of age-related macular degeneration (AMD). Neuroretina sparing laser therapies, thermal stimulation of the retina (TSR) and selective retina therapy (SRT), are known to reduce AMD-like pathology in vitro and in vivo. We investigated the effect of TSR and SRT on inflammatory processes in AMD mouse models. Methods: One randomized eye of 8 months old apolipoprotein (Apo)E and 9 months old nuclear factor (erythroid-derived 2) -like 2 (NRF2) knock out mice were treated by TSR (10 ms, 532 nm, 50 µm 2 spot size, mean 4.5 W, ~200 spots) or SRT (~1.4 µs pulses, 532 nm, 50 µm spot size, 100 Hz over 300 ms, mean 2.5 µJ per pulse, ~200 spots). Fellow eyes, untreated knock out mice and wild-type BL/6J mice acted as controls. All mice were examined funduscopically and by optical coherence tomography (OCT) at the day of laser treatment. Mice were euthanized and enucleated either 1 day or 7 days after laser treatment and examined by gene expression analysis of 84 inflammatory genes. Results: The inflammatory gene expression profile of both knock out models compared to healthy BL/6J mice suggests a regulation of pro- and anti-inflammatory processes especially concerning T-cell activity and immune cell recruitment. TSR resulted in downregulation of several pro-inflammatory cell-mediators both in ApoE -/- and NRF2-/- mice compared to treatment naïve litter mates one day after treatment. In contrast, SRT induced pro-inflammatory cell-mediators connected with necrosis one day after treatment as expected following laser-induced selective RPE cell death. Seven days after laser treatment, both findings were reversed. Conclusions: Both TSR and SRT influence inflammatory processes in AMD mouse models. However, they act conversely. TSR leads to anti-inflammatory processes shortly after laser therapy and induces immune-cell recruitment one week after treatment. SRT leads to a quick inflammatory response to laser induced RPE necrotic processes. One week after SRT inflammation is inhibited. It remains unclear, if and to what extent this might play a role in a therapeutic or preventive approach of both laser modalities on AMD pathology.